High breakdown strength and low loss of polystyrene-block-poly(methyl methacrylate)/Poly(vinylidene fluoride) composites for energy storage application. Issue 11 (24th July 2019) - Yang, Bing; Qu, Peng; Peng, Xiaohan; Liu, Xiaolin
ABSTRACT: Poly(vinylidene fluoride) (PVDF) composite films were prepared by introducing polystyrene-block-poly(methyl methacrylate) (PS-b-PMMA) into PVDF matrix. Uniform dispersion and good compatibility of PS-b-PMMA in matrix were observed, which was helpful for high breakdown strength ( Eb ). The composite film with 9 wt% PS-b-PMMA showed the maximum Eb of 522 kV/mm and the high discharged energy density ( Ue ) of 10.1 J/cm 3, which were 1.7 times and 2.6 times higher than pure PVDF, respectively. Besides, a charged-discharged efficiency ( η ) of 88% was much higher than pure PVDF at 300 kV/mm, which was beneficial to energy storage. Graphical Abstract: